Anti-inflammatory effect and mechanisms of Huangqi glycoprotein in treating experimental autoimmune encephalomyelitis - Zhang, Huiyu; Guo, Minfang; Zhang, Lihong; Xue, Huiqing; Chai, Zhi; Yan, Yuqing; Xing, Yanxia; Xiao, Baoguo; Zhang, Peijun; Ma, Cungen (Folia Neuropathologica, 2017)
Huangqi glycoprotein (HQGP) is prepared from Astragalus membranaceus by ammonium sulfate precipitation. It was indicated that HQGP has an immunoregulatory effect. In this study, we established a chronic experimental autoimmune encephalomyelitis (EAE) model and observed the therapeutic effect and possible mechanisms of HQGP (intraperitoneally at 1 mg/kg/day) on EAE. The results showed that HQGP delayed onset and ameliorated severity of EAE, and reduced the infiltration and accumulation of pathogenic T cells in the central nerves system (CNS). HQGP also reduced the production of IL-6, IL-17 and TNF-α and increased the level of IL-10. However, the level of IFN-γ production was also increased in HQGP-treated mice compared with EAE control mice. In brain, chemokines such as CCL2 and CCL5 were inhibited in HQGP-treated EAE compared with control mice. These results demonstrate that HQGP alleviates the pathogenesis of EAE possibly by suppressing the neuroinflammation and decreasing the secretion of chemokines and cell adhesion.